Legal basis of the innkeeper obligation to ensure the physical safety of the guest in Iraqi and Egyptian law: A comparative study with the French and English laws - نهاي سعد حسون; الساعدي جليل حسن (Journal of Legal Sciences, 2021)
The legal basis for the obligation of the innkeeper to ensure the safety of things does not pose any problem, because the comparative legislation was organized by explicit legal texts, but the problem arises with regard to the legal basis of the innkeeper’s obligation to ensure the physical safety of the guest, as these legislation lacked explicit provisions about it, and left the organization of the general rules, which Open the door to jurisprudence, where the foundations laid by the jurists, within the scope of civil law, unlike the English legislator, which organized it as a general duty in the landlord law of 1957, and some consumer protection laws implicitly referred to the obligation of the innkeeper To ensure the safety of the body of the guest, the aim of this study is to identify the legal basis of this obligation and to achieve this goal we must first show the legal basis for this obligation in the Civil Code, and then clarify its legal basis in the Consumer Protection Act.